DETERMINASI KEPUTUSAN GENERASI Z MEMBELI KOPI KELILING DI KOTA BANJARMASIN - Sucidha, Irma; Irayana, Ika (POLITEKNIK LP3I JAKARTA, 2025)
The phenomenon of mobile coffee (Starling/Kopling) has become an informal business model that has transformed the coffee consumption landscape in Indonesia, including in Banjarmasin, by offering high accessibility and affordable prices. This study aims to analyze and identify the most dominant determining factors influencing the Purchase Decisions of Generation Z in Banjarmasin. This quantitative research uses an explanatory cross-sectional design with 105 Generation Z respondents in Banjarmasin, selected through accidental sampling, where the majority of respondents are students (49.52%). The independent variables examined are Product Quality (X1), Price (X2), Location/Access (X3), Promotion/Social Media (X4), Brand Image (X5), and Service Quality (X6) on Purchase Decision (Y). Partially (t-test), four variables were proven to have a significant effect: Product Quality (X1), Location/Access (X3), Brand Image (X5), and Service Quality (X6). Based on the regression coefficient values, Brand Image (0.300) is the most dominant factor, followed by Service Quality (0.250). Meanwhile, Price (X2) and Promotion/Social Media (X4) do not have a significant effect. These findings highlight that amidst the homogeneity of mobile coffee prices, psychological and social factors reflected in brand image, product quality, and service become the main determinants of Purchase Decisions for Generation Z.